A novel attenuated and marker M. bovis-BoAHV-1 combined vaccine provides broad protection against diverse bovine alphaherpesvirus type 1 genotypes - Sen Zhang; Guoxing Liu; Zhijie Xiang; Jianguo Chen; Aizhen Guo; Yingyu Chen (Virulence, 2025)
Mycoplasma bovis (M. bovis) and bovine alphaherpesvirus 1 (BoAHV-1) are two major infections that seriously impair cattle’s reproductive and respiratory systems. We created an M. bovis-BoAHV-1 combined vaccine and assessed its safety and effectiveness in our earlier work. This study evaluated a novel combined vaccine comprising attenuated M. bovis and marker BoAHV-1 antigens for its immunogenicity and efficacy in protecting cattle against diverse BoAHV-1 genotypes. The cattle were divided into four groups: M. bovis-BoAHV-1 combined vaccine, inactivated vaccine, non-immune challenge, and blank control groups. RT-PCR was used to assess viral shedding after the groups challenged with either the BoAHV-1 1.1a or 1.2b strains. The results demonstrated that the combined vaccine group prompted a high degree of production of cytokines, B cells, and T cell-associated signaling pathways and was able to elicit considerably greater antibody titers (p < 0.01). Under experimental challenge conditions, the combined vaccine reduced BoAHV-1 viral shedding by 70% in vaccinated cattle compared to controls, shorter duration of virus shedding was also observed in the vaccinated groups compared to the non-immune challenge group for different BoAHV-1 strain challenges, about 6–8 d earlier clearance of virus shedding compared to the non-immune challenge group. Notably, the combined vaccine provided cross-protection against multiple BoAHV-1 genotypes, demonstrating its potential as a broad-spectrum solution for controlling bovine respiratory disease. These findings providing important insights into effective disease control strategies for cattle herds.